Sclerosing Angiomatoid Nodular Transformation of the Spleen: A Case Report (Central Asian Journal of Medical Sciences, 2019)
Objectives: Sclerosing Angiomatoid Nodular Transformation (SANT) of the spleen is a rare benign vascular lesion with unknown etiology. Our purpose is to present our experience with this condition and review the available literature regarding it. Methods: This report depicts a pathologically proven case of SANT in a 32-year-old man with a history of two previous old injuries who presented with weight loss, vomiting and with left upper quadrant pain and an enlarged spleen. Results: The patient was successfully treated by splenectomy and diagnosed with SANT based on histological and immunohistochemical findings postoperatively. Conclusion: Most patients with SANT are asymptomatic. Imaging studies are essential for detection and the management of SANT. However, the final diagnosis can only be made by histopathology. SANT does not recur after splenectomy.